Melatonin treatment improves postharvest quality and regulates reactive oxygen species metabolism in “Feizixiao” litchi based on principal component analysis - Xie, Jing; Qin, Ziyi; Pan, Jiali; Li, Jing; Li, Xia; Khoo, Hock Eng; Dong, Xinhong (Frontiers in Plant Science, 2022)
Postharvest quality of litchi reduces rapidly during storage at room temperature. This study aimed to investigate the effect of melatonin treatment on postharvest quality and oxidative stress markers of litchi fruit during cold storage. The “Feizixiao” litchi was treated with melatonin solution concentrations of 0.2 mmol·L-1 and 0.6 mmol·L-1 and then stored at 4°C for 12 days. The results confirmed that the melatonin treatment effectively maintained the appearance and color of the litchi fruit, suppressed the peel browning, and improved the litchi quality. The treatment also significantly enhanced the levels of endogenous melatonin, antioxidant components (total phenolics, flavonoids, and anthocyanin), and antioxidant enzyme activities of the fruit. It also inhibited the other oxidative stress markers, such as O2−, H2O2, MDA, and protein carbonyl content, and upregulated the expressions of antioxidant and Msr-related genes. Correlation and principal component analyses further confirmed that the melatonin treatment effectively delayed the fruit senescence by enhancing the antioxidant enzyme activities and modulating peel browning and reactive oxygen species metabolism of the litchi fruit via regulating gene expression of the related enzymes (SOD and PPO). These findings suggested that the exogenous application of melatonin to litchi during the postharvest is an ideal way to preserve the fruit quality and delay fruit senescence.